MULTIDRUG RESISTANCE OF SHEEP GASTROINTESTINAL NEMATODES IN BAKRAJO DISTRICT, NORTH IRAQ TO ALBENDAZOLE, IVERMECTIN, AND LEVAMISOLE - & Qader, Othman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A survey including 25 sheep farms in Bakrajo District, Sulaymaniyah, Iraq, was conducted to determine anthelmintic resistance (AR) against albendazole, ivermectin, and levamisole. Fecal Egg Count Reduction Test (FECRT) was used to accomplish this goal. Forty 6–24 month-old sheep of mixed sexes were selected from each farm and randomly divided into four groups. One group served as the untreated control, and the other groups orally administered the recommended doses of the tested drugs. Multidrug resistance against all three drugs was present in 8 of 25 farms (32%). Also, resistance to albendazole and ivermectin was detected on one farm. Albendazole was the most effective anthelmintic agent. Resistance to ivermectin was significantly higher than levamisole and albendazole. Larval cultures revealed that Trichostrongylus spp., Nematodirus spp., and Trichuris spp. were the prevalent gastrointestinal nematodes in the study area. The nematode genera were also detected in the posttreatment larval cultures. It is concluded that AR to albendazole, ivermectin, and levamisole is widespread in sheep in Bakrajo District, north Iraq. This resistance is mainly caused by the emergence of resistant Trichostrongylus and Nematodirus spp.